Spatial–temporal evolution and influencing factors of the eco-efficiency of cultivated land-use in the Beijing–Tianjin–Hebei region in the context of food security - Jiao, Xinying; Ma, Jingtao; Liu, Guoxiang; Li, Yancang; Li, Chenggang; Wang, Xin (Frontiers in Sustainable Food Systems, 2024)
Improving the eco-efficiency of cultivated land use (ECLU) is important for ensuring food security, promoting social and economic development, and reducing carbon emissions. However, dynamic inter-period comparisons of the ECLU and clarifications of its influencing factors are limited. We calculated the ECLU at the county level in the Beijing-Tianjin-Hebei region, China, based on the super-efficiency slacks-based measure and global Malmquist-Luenberger index and analyzed its influencing factors utilizing a geographically and temporally weighted regression model. From 2000 to 2020, the number of higher counties decreased and that of medium counties increased.Geographically, the ECLU values in the north are higher than those in other districts and counties; counties in Beijing and Tianjin maintained moderate ECLU values, whereas Zhangjiakou and Chengde maintained high ECLU values. The ECLU value in the study area showed a trend of rapid decline-slow rise-continuous rise, with the upward trend of the ECLU value in Beijing-Tianjin-Hebei region being significantly less pronounced than those in most counties of Hebei Province.Resource allocation and scale expansion where initially dominant; however, technological progress and investment eventually prevailed. The ECLU is mainly affected by the multiple cropping index, industrial structure, irrigation index, mechanized farming level, and per capita cultivated land. This study assesses the ECLU in the Beijing-Tianjin-Hebei region, providing a scientific basis for the formulation and implementation of relevant policies for its improvement. Furthermore, this study enriches the theory and methods of research on the ECLU and has practical value and theoretical significance. Overall, the results have important social value as they contribute to ensuring national food security, reducing carbon emissions, promoting regional coordinated and sustainable development.